Design, Optimization, and Evaluation of Combined Dosage form of Amoxicillin and Nonsteroidal Anti-inflammatory Agent for Pediatric use using DoE - Al-Ani, Israa H. (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Combination therapy is gaining high attention in pharmaceutical industry. It provides many advantages in accuracy of dose and patient compliance, especially in pediatrics. This work aims to formulate successful fixed-dose combination pediatric oral dosage form as orodispersible tablets (ODTs) which contain a combination of amoxicillin 125 mg as an antibiotic and ibuprofen 100 mg per tablet for the treatment of several pediatric illnesses that need this combination. Materials and Methods: Design of experiment (DoE) was used to design the best formula for the proposed combination. The selection of non-active materials based on the improvement of tablet characteristics, taste, and safety. Then, DoE was used to predict the best combination of additives that give the best criteria of ODTs. The three responsive factors were wetting time and disintegration time and dissolution of both drugs taken as 70% of drug is dissolved at or in <30 min. Moreover, the three materials which were found to affect these responsive factors are sodium starch glycolate, Avicel, and sucrose. The optimized formula then was prepared and evaluated. Results and Discussion: Results were treated and the best combination of the affecting materials was confirmed by DoE that fitted the criteria of ODT. The optimized formula gave results which were very close to the predicted results by the DoE regarding the three response factors. Conclusion: Successful design was achieved using DoE, economic, and easy in production and achieved the goals of the design.